Modification of the Lee-Carter mortality model and its application in the pension scheme - Rossa, Agnieszka (Publishing House of Wroclaw University of Economics and Business, 2022)
In this paper, a new approach to mortality forecasting is proposed based on an improved model of the Lee-Carter type. The standard Lee-Carter model and its modified version were introduced and compared using mortality data for Poland and some other European countries. Forecasts of log-central age-specific death rates were then derived and used to predict death probabilities and life expectancies for males and females in Poland, which are the main parameters of the so-called dynamic life tables (also known as mortality tables). The application of the proposed methodology in calculations of the present values of future pension annuities is presented in the article. Scenarios of monthly pensions obtained with the use of dynamic life tables were considered and compared with analogous scenarios based on the static (period) life tables published every year by the Central Statistical Office of Poland.
Argumenta Oeconomica, 2022, Nr 2 (49), s. 93-113
Keywords: mortality forecasting; Lee-Carter model; dynamic life tables; pension annuities